2022
DOI: 10.3390/d14080587
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi Associated with Roots Reveal High Diversity Levels at Different Elevations in Tropical Montane Rainforests

Abstract: (1) Background: Understanding the diversity of communities of arbuscular mycorrhizal fungi (AMF) is the basis for understanding the ecological functions of AMF. (2) Methods: The community diversity and distribution of AMF at different elevations in tropical montane rainforests of Mt. Jianfenfling and Mt. Diaoluo were explored using high-throughput sequencing technology. (3) Results: A total of 283 AMF operational taxonomic units (OTUs) were identified from roots and the number of unique OTUs was 173, accountin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, pH and AP were highly significantly and negatively correlated with community diversity. It is possible that pH can affect not only the formation and development of AMF spores (Zhang et al, 2022a), but also indirectly by affecting plant community composition and plant uptake and utilization of soil nutrients (Xu et al, 2017). The effect of AP on AMF community diversity is consistent with the findings of Ji and Bever (2016) and Ceulemans et al (2019), possibly because elevated AP levels inhibit AMF spore germination and mycelial growth and cause plants to reduce root symbiosis with AMF and take up P directly from the soil (Johnson et al, 2015;Shi et al, 2021).…”
Section: Influencing Factors Of Soil Arbuscular Mycorrhizal Fungi Com...mentioning
confidence: 99%
“…Furthermore, pH and AP were highly significantly and negatively correlated with community diversity. It is possible that pH can affect not only the formation and development of AMF spores (Zhang et al, 2022a), but also indirectly by affecting plant community composition and plant uptake and utilization of soil nutrients (Xu et al, 2017). The effect of AP on AMF community diversity is consistent with the findings of Ji and Bever (2016) and Ceulemans et al (2019), possibly because elevated AP levels inhibit AMF spore germination and mycelial growth and cause plants to reduce root symbiosis with AMF and take up P directly from the soil (Johnson et al, 2015;Shi et al, 2021).…”
Section: Influencing Factors Of Soil Arbuscular Mycorrhizal Fungi Com...mentioning
confidence: 99%
“…On the one hand, they obtain nutrients from plants to complete their own growth and development [ 9 ]; on the other hand, they can also improve the host plant, improve the root surface area and inter-root absorption range of the host plant, and increase the ability to absorb water and nutrients from the soil, playing an important role in plant growth and development [ 5 ]. Previous studies showed that environmental factors obviously affected arbuscular mycorrhizal fungi growth and distribution [ 10 , 11 , 12 ]. Forest fires, as an important disturbance factor in forest ecosystems, have a profound effect on arbuscular mycorrhizal fungi composition and function though changing soil nutrients, e.g., forest fires have a significant effect on arbuscular mycorrhizal fungi infestation rate, species composition, density, and reproduction [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies showed that the soil AMF had no response to the diversity and productivity of vegetation (Bauer et al, 2015). In pasture and secondary natural succession, the biomass and catabolic diversity of soil microbial communities were regulated by soil organic carbon (SOC) and soil nitrogen (SN) (Iyyemperumal et al, 2007;Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%